2019
DOI: 10.32615/ps.2019.095
|View full text |Cite
|
Sign up to set email alerts
|

Light-response curve of photosynthesis and model fitting in leavesof Mangifera indica under different soil water conditions

Abstract: A pot experiment was performed to study the light-response curve of photosynthesis (PN-PAR curve) of Mangifera indica and the applicability of light-response models under different soil water conditions. The experimental data were fitted and analyzed using the rectangular hyperbola model, the nonrectangular hyperbola model, the exponential model, the modified rectangular hyperbola model, and the kinetic model. The results showed that the optimal range of relative soil water content (RSWC) for the normal photos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 35 publications
(50 reference statements)
1
26
0
Order By: Relevance
“…Soil drought would suppress photosynthesis in plants to some extent, thus affecting PNmax. It was found that PNmax significantly decreased with the decrease of soil water content (Xu et al 2013, Li et al 2019. In this study, SWC ranged between 39-61% of the field capacity.…”
Section: Correlations Of Photosynthetic Parameters Obtained Bymentioning
confidence: 52%
See 4 more Smart Citations
“…Soil drought would suppress photosynthesis in plants to some extent, thus affecting PNmax. It was found that PNmax significantly decreased with the decrease of soil water content (Xu et al 2013, Li et al 2019. In this study, SWC ranged between 39-61% of the field capacity.…”
Section: Correlations Of Photosynthetic Parameters Obtained Bymentioning
confidence: 52%
“…Many studies showed that the Ye model had a greater simulation effect compared to other four light-response models (Ye 2007, Zheng et al 2012, Lang et al 2013, Ren et al 2017, while the fitting capacity of RH model was the worst (Li et al 2019). AQY obtained by RH model was often higher than the measured value (Gomes et al 2006, Ye 2007, Xia et al 2014.…”
Section: Comparison Of Different Light-response Modelsmentioning
confidence: 99%
See 3 more Smart Citations